Analysis of Inventory Control of Raw Materials for Cotton Fabric Using the Economic Order Quantity Method - Chairunnisa, Ananda; Surachman (Jurnal Management Risiko dan Keuangan, 2025)
PT Sansan Saudaratex Jaya Cibaligo still has not implemented a specific method for controlling the supply of fabric raw materials cotton, which causes excess inventory every month and makes the total inventory costs not well controlled. Inventory costs can be minimized by using the method Economic Order Quantity (EOQ). The EOQ method not only helps in determining the optimal order quantity, but also the optimal purchase frequency, safety stock, and the right time to place a reorder. The aim of this research is to determine and optimize raw material supplies at PT Sansan Saudaratex Jaya Cibaligo using the EOQ method. Data collection was carried out through interview and documentation techniques, while the data analysis method used was EOQ, which includes calculating purchase frequency, Total Inventory Cost (TIC), Safety Stock, And Re-Order Point. The results of data analysis using the EOQ method show lower total inventory costs compared to conventional methods, which in the end can significantly increase cost efficiency and overall company profits.